Multi-omic analysis of host-microbial interactions central to the gut-brain axis. (28th September 2022) - Simpson, Joshua B.; Redinbo, Matthew R.
Abstract : The neurotransmitters serotonin and dopamine reside in the gastrointestinal tract and impact host physiology and neurological disease states. Emerging technologies for investigating the gut microbiome can be integrated towards solving the molecular mechanisms linking the gut microbiota to neurological functions. Abstract : The gut microbiota impact numerous aspects of human physiology, including the central nervous system (CNS). Emerging work is now focusing on the microbial factors underlying the bi-directional communication network linking host and microbial systems within the gastrointestinal tract to the CNS, the "gut-brain axis". Neurotransmitters are key coordinators of this network, and their dysregulation has been linked to numerous neurological disease states. As the bioavailability of neurotransmitters is modified by gut microbes, it is critical to unravel the influence of the microbiota on neurotransmitters in the context of the gut-brain axis. Here we review foundational studies that defined molecular relationships between the microbiota, neurotransmitters, and the gut-brain axis. We examine links between the gut microbiome, behavior, and neurological diseases, as well as microbial influences on neurotransmitter bioavailability and physiology. Finally, we review multi-omics technologies uniquely applicable to this area, including high-throughput genetics, modern metabolomics, structure-guided metagenomics, targeted proteomics, and chemogenetics. Interdisciplinary studies will continue to drive the discovery of molecular mechanisms linking the gut microbiota to clinical manifestations of neurobiology.